Pengaruh Sosial Ekonomi Terhadap Tingkat Kekritisan Lahan Pada Kawasan Budidaya Pertanian (Studi Kasus Desa Ngabab Kecamatan Pujon) - Hakim, Annisa Nurul; Anggraeni, Mustika; Dinanti, Dian (Jurnal Tata Kota dan Daerah, 2014)
Population growh affects the increasing needs for food and agricultural land, while the existence of agricultural land is reduced. Efforts to increase agricultural product by using chemical fertilizers and pesticides have negative impact on the environment. Insistence of the fulfillment of economic needs affected to the exploitation of agricultural land that can trigger critical land. Most villagers work as a farmer, which is identical with low level of welfare. Increasing poverty rate among farmers will continue if the critical condition of agricultural land increasingly widespread because farmers will lose their jobs. It will caused socio-economics impacts, namely the broader unemployment, crime, and decreased quality of life. This study aimed to determine critical land level on agricultural land and whether there is influence between socio economic condition with the critical land level. The methods used to measure the critical land level were overlay, scoring, and weighting. The critical level divided into five categories, are very critical, critical, medium critical, potential critical, and uncritical area. The analysis methods used to measure correlation between socio economic with crtical land level was multiple linear regression analysis. Based on the overlay analysis showed that critical land level on samples are Critical 0,957 ha, Medium Critical 10,473 ha, Potential Critical 6,24 ha, and Uncritical 1,247 ha. The result of regression analysis showed that there was significant influence between the socio economic and critical land level. The significant variables on farmer samples are agricultural counseling frequencies, per capita income, and farm product with the model is Y = 179,452 + 18,672X1 + 10,394X4 + 3,278X5. Meanwhile for the landowner samples, the significant variables are per capita income and farm product with the model is Y = 308,342 + 4,729X4 + 2,043X5. Regression results were positif it means, the lower socio economic conditions, the land become more critical. Keywords: critical land level, socio economic, agricultural, regression